LA RESTAURACIÓN DEL ACLLAWASI EN EL SANTUARIO DE PACHACAMAC, 1940-1944. IDENTIFICANDO LAS HUELLAS DE VIOLLET-LE-DUC, UN ANÁLISIS COMPARATIVO - Asencios Lindo, Rodolfo Gerbert (2017)
The restoration of the Acllawasi or Temple of the Mamaconas represents one of the first large-scale interventions carried out in the Sanctuary of Pachacamac. It owes its importance not only to the fact that Julio C. Tello executed it between 1940 and 1944, but also to the monument’s importance among the buildings that make up the sanctuary. Nonetheless, despite its transcendence, little is known about the goals and ends that determined the restoration of this edifice. Thus, through an appraisal of publications, newspaper clippings, and unpublished documents, this paper sketches the first overview of the restoration process. It also illustrates the application, in the project, of the principles and proposals of Viollet-le-Duc, the main representative of European stylistic restoration. The analysis presented here will therefore allow readers to know about the history of archaeological conservation in Peru.